ERI Energy thesaurus - Blomkamp, Yvonne (Library and Information Studies Centre (LISC), 2023)
Although numerous dictionaries of energy terms are available, and there are other thesauri on specific aspects of energy, for example, coal, biomass, nuclear energy, there are few comprehensive energy thesauri. So far, no energy thesaurus applicable to South Africa, has been published. It was found that energy terms in the U.S. Department of Energy's Energy Data Base: Subject Thesaurus are used in a different context to South Africa. The United Kingdom in - turn, used terms in a different context to the United States. In order for there to be effective cooperation between information centres engaged in the collection, storage and dissemination of energy-related information in South Africa, a need was perceived for the definition and standardisation of the terms and concepts used in the energy field. In recognition of this need, the CSIR provided funds for a year to develop an energy thesaurus relevant to South Africa.